2001
DOI: 10.1081/clt-100108512
|View full text |Cite
|
Sign up to set email alerts
|

Neurotoxicology of the Brain Barrier System: New Implications

Abstract: The concept of a barrier system in the brain has existed for nearly a century. The barrier that separates the blood from the cerebral interstitial fluid is defined as the blood-brain barrier, while the one that discontinues the circulation between the blood and cerebrospinal fluid is named the blood-cerebrospinal fluid barrier. Evidence in the past decades suggests that brain barriers are subject to toxic insults from neurotoxic chemicals circulating in blood. The aging process and some disease states render b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
67
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 105 publications
(69 citation statements)
references
References 72 publications
2
67
0
Order By: Relevance
“…10,16,20,45 A predominant intracellular overload of iron and subsequent iron-mediated oxidative stress may lead to damage of neurons. Results in this study showed that exposure to the welding fume significantly increased the concentration of iron in serum.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…10,16,20,45 A predominant intracellular overload of iron and subsequent iron-mediated oxidative stress may lead to damage of neurons. Results in this study showed that exposure to the welding fume significantly increased the concentration of iron in serum.…”
Section: Discussionmentioning
confidence: 99%
“…In the current human study, the career welders did show a significantly higher Although the precise mechanism by which manganese induces neurodegenerative toxicity is poorly understood, evidence suggests that manganese toxicity may be partly the result of its action on iron homeostasis. 10,16,20,45 A predominant intracellular overload of iron and subsequent iron-mediated oxidative stress may lead to damage of neurons. Results in this study showed that exposure to the welding fume significantly increased the concentration of iron in serum.…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 99%
See 2 more Smart Citations
“…Brain barriers contribute to the etiology of AD mainly in three aspects: (i) the aging of cerebral vascular structure in the overall aging process of the brain, (ii) as the site of transport of extracerebral Aβ into the brain, and (iii) the ability to prevent Aβ aggregation by removing it (Zheng, 2001). The blood-brain barrier (BBB) separates blood from the interstitial fluid surrounding the neurons and neuroglia, and the blood-CSF barrier (BCB) separates the blood and CSF in and around the brain.…”
Section: Introductionmentioning
confidence: 99%